EFISIENSI PENGGUNANFAKTOR-FAKTOR PRODUKSI PADA USAHA PEMBESARAN IKAN NILA (Oreochromis niloticus) - Yusnita Primawati; Rina Nuryati; Zulfikar Noormansyah (Universitas Galuh, 2023)
The use of production factors (ponds, seeds, organic fertilizers, lime, feed and labor) in tilapia growing business is a factor that plays an important role in determining the level of efficiency. This study aims to determine and analyze the efficiency of the use of production factors in tilapia enlargement business, namely technical efficiency, factors that affect the level of technical inefficiency, allocative and economic efficiency. The research method uses a survey method. The determination of the research location was carried out purposively in the City of Tasikmalaya. Determination of samples taken from a population of 314 people using the proportional random sampling method obtained 76 cultivators of tilapia enlargement business. The research was conducted from March to July 2022. Data were analyzed using the stochastic frontier production function model and the dual frontier cost function using Frontier 4.1 software. The results showed that the use of production factors in tilapia rearing business was not efficient with an average technical efficiency level of 0.68 and the factors influencing technical inefficiency were business experience and the number of family dependents; the average allocative efficiency level is 0.76; and the average economic efficiency of 0.53